Genomic and Functional Characterization of Enterococcus mundtii QAUEM2808, Isolated From Artisanal Fermented Milk Product Dahi - Nawaz, Farah; Khan, Muhammad Nadeem; Javed, Aqib; Ahmed, Ibrar; Ali, Naeem; Ali, Muhammad Ishtiaq; Bakhtiar, Syeda Mariam; Imran, Muhammad (Frontiers in Microbiology, 2019)
Microbial strains having unique combination of technological and bioactive properties are a preferred for industrial applications. Present study was conducted to evaluate the potential use of Enterococcus mundtii QAUEM2808 (NCBI Acession Number: LSMC00000000) in milk fermentation. The strain was isolated from Dahi, an indigenous fermented milk product of South-East Asia. The in vitro study confirmed the acidification ability as well as the proteolytic, cellulolytic and amylolytic enzyme activities of this strain. It also produced substaintial amount of the folate in labotory media besides, no physiological dysfunctions to labotory animal was observed in feeding trials. All these properties were confirmed by in sillico genome anlaysis. The Enterococcus mundtii QAUEM2808 genome consisted of a single, circular chromosome consist of 2,957,300-bp, 2,587 genes with GC content of 38.5 %. Moreover, 16t RNAs, 1, 3 (16S, 23S) rRNAs, 4 ncRNAs and 91 pseudo genes were also predicted. The genome having all genes required for lactic acid production beside presence of genes encoding for protein, amino acids and also carbohydrate metabolisms. It also exhibited antimicrobial activity against E. coli ATCC 10536, S. aureus ATCC 6538, P. aeruginosa ATCC 9027 and L. monocytogenes ATCC 13932 and was found to be sensitive to commonly used antibiotics. The in silico analysis revealed the presence of genes for mundaticin and enterocin production, and CRISPER regions, however, the genes for antibiotic resistance were absent. No genes related to pathogenicity island and prophages were detected by genome mining. Therefore, it could be inferened that Enterococcus mundtii QAUEM2808 have the potential to be used in milk fermentation as adjunct culture.